Interphase argyrophilic nucleolar organiser regions and nucleolar counts in transitional cell bladder tumours. Issue 3 (1st June 2000) - Korneyev, I A; Mamaev, N N; Kozlov, V V; Rybakova, M G; Al-Shukri, S H
Abstract : Aims —To see whether a correlation exists between clinicopathological parameters, argyrophilic nucleolar organiser regions (AgNORs), and nucleolar counts in the nuclei of tumour cells in patients with transitional cell bladder carcinoma. Methods —Paraffin wax embedded sections from a total of 62 cases of primary transitional cell bladder carcinoma were stained with the silver colloid method. The numbers of individual silver grains (AgNORs) in nucleoli and the numbers of nucleoli were counted in 100 nuclei. The correlation between AgNORs and nucleolar counts and patients' sex, tumour grade, disease stage, recurrence pattern, and tumour related survival was analysed. Results —The numbers of nucleoli in tumour cells were higher in male patients (p < 0.032). AgNOR numbers correlated with tumour grade (p = 0.017) and recurrence (p = 0.046). In multivariate analysis, the variation coefficient of AgNOR scores was found to be the only independent predictor of the duration of tumour free period in patients with recurrent disease (p < 0.002). AgNOR scores and nucleolar counts were of no value in distinguishing superficial and invasive tumours or in predicting tumour related survival. Conclusions —AgNOR scores in transitional cell bladder carcinoma reflect variations in tumour biological behaviour; however, the clinical value of this technique in patients with urinary bladder carcinoma is limited.